Bloodhound - Pierce, Tamora (Pierce, Tamora. Beka Cooper, 2009)
Having been promoted from "Puppy" to "Dog," Beka, now a full-fledged member of the Provost's Guard, and her former partner head to a neighboring port city to investigate a case of counterfeit coins.